2001
DOI: 10.2460/ajvr.2001.62.1436
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of concurrent shedding of bovine coronavirus via the respiratory tract and enteric route in feedlot cattle

Abstract: Feedlot cattle infected with BCV after transport shed BCV from the respiratory tract and in the feces. Fecal shedding of BCV was associated with significantly reduced weight gain. Developing appropriate control measures for BCV infections could help reduce the decreased weight gain observed among infected feedlot cattle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
103
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(112 citation statements)
references
References 24 publications
(34 reference statements)
7
103
1
1
Order By: Relevance
“…In earlier investigations by our group and in other studies it was reported that cattle of this age group were shedding BCoV especially after entering the feedlot (Hasoksuz et al, 1999a;Lathrop et al, 2000b;Cho et al, 2001b). The aim of this investigation was to detect BCoV in three different age groups of cattle (0-30 days old, 4-12 months old and 2-7 years old) with respiratory and/or diarrhoeic signs detected in their barn, and in animals that had been living for more than three months on the same farm.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In earlier investigations by our group and in other studies it was reported that cattle of this age group were shedding BCoV especially after entering the feedlot (Hasoksuz et al, 1999a;Lathrop et al, 2000b;Cho et al, 2001b). The aim of this investigation was to detect BCoV in three different age groups of cattle (0-30 days old, 4-12 months old and 2-7 years old) with respiratory and/or diarrhoeic signs detected in their barn, and in animals that had been living for more than three months on the same farm.…”
Section: Discussionsupporting
confidence: 51%
“…In the early 1980s, Thomas et al (1982) first isolated BCoV from lung washes and nasopharyngeal swabs from calves involved in two outbreaks of pneumonia. Subsequently, respiratory bovine coronavirus (RBCoV) strains were frequently detected by ELISA and isolated from nasal swab samples of feedlot cattle with respiratory tract disease after shipping (Saif et al, 1986;Tsunemitsu et al, 1991;Storz et al, 2000a;Cho et al, 2001b;Hasoksuz et al, 2002). Cattle shedding BCoV nasally after entering the feedlot were at an increased risk of developing respiratory disease (Lathrop et al, 2000a) and had high mortality due to BCoV infection (Storz et al, 2000b).…”
mentioning
confidence: 99%
“…10,27,32,39,40,54,71 An association between nasal shedding of BoCV and clinical signs of respiratory disease has been reported in some studies 32,66,67,71 but not others.…”
Section: Discussionmentioning
confidence: 99%
“…BCoV is the causative agent of neonatal calf diarrhoea (CD), winter dysentery (WD) in adult cattle (Alenius et al, 1991;Mebus et al, 1973;Saif et al, 1988) and respiratory tract disorders in cattle of all ages (Cho et al, 2001;Decaro et al, 2008a;Lathrop et al, 2000). This infection is not effectively controlled in the herds by current commercial vaccines (Saif, 2010).…”
Section: Introductionmentioning
confidence: 99%